Pengaruh Live Streaming Video Promotion, Diskon Harga, Online Costumer Review Saat Live Streaming Tiktok Terhadap Keputusan Pembelian - Riska Dwi Arrohma; Budi Istiyanto (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
The purpose of this study is to determine the effect of live streaming video promotion, price discounts and online customer reviews when live streaming Tiktok on purchasing decisions. This research method uses quantitative methods with data analysis using instrument data tests, classical assumption tests, and multiple linear regression analysis using the SPSS application. The sampling method used is non-probability sampling with purposive samp ling techniques. The number of samples obtained by 140 respondents who had shopped through Tiktok live streaming in Solo Raya. The results of this study show that the variables of the influence of live streaming video promotion, price discounts and online customer reviews have a significant partial effect on purchasing decisions on Tiktok live streaming. While the variables The influence of live streaming video promotion, price discounts and online customer reviews simultaneously has a significant effect on purchasing decisions through Tiktok live streaming.